PERAN PENGHULU TERHADAP PELAKSANAAN PASAL 39 UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Syamsurrizal, Entus; Sari, Yani Kurnia (Direktorat Jenderal Bimbingan Masyarakat Islam, 2018)
Divorce is an important part of human life. When relationships are fostered through marriage cannot be maintained, divorce is permitted. Islamic law regulates marriage and divorce in quite detailed, Islamic jurists (fuqaha) argue if someone utters the words talak or others against his wife then the divorce is considered valid. Meanwhile, positive law (Law No. 1/1974 and PP. 9/1975 concerning the Implementation of Law No.1 / 1974 confirms that